Digitalisasi Manajemen Kegiatan Kelompok Kerja Guru Menggunakan Teknologi Web - Ramlah, Ramlah; Utami, Listia; Sulehu, Marwa; Ratnawati, Ratnawati; Idris, Nur Idil Fitri; Mashud, Mashud (TIN: Terapan Informatika Nusantara, 2025)
Teacher Working Group (KKG) is a professional forum for teachers to improve their competence and collaboration through routine activities such as training, preparation of teaching materials, and discussions on education policies. However, these activities are often hampered by manual management resulting in information delays, data duplication, and unstructured documentation. This study aims to design and implement an integrated and efficient web-based KKG activity management information system. The study was conducted in Cluster 3, Mamajang District, Makassar City. The method used is the Waterfall software development model, with data collection techniques through observation, interviews, and literature studies. System testing was carried out using the black box method to ensure that the system's functionality runs according to plan. The implementation results show that the system can manage membership data, activity schedules, documentation reports, and internal notifications effectively. The test results show that all system functions run well. This digitalization has been proven to support the efficiency of KKG activity management and has the potential to be adopted more widely in the context of improving the quality of basic education.